The Effect of User Satisfaction of the Custom Excise Information System & Automation (CEISA) System on User Trust to Improve Customs Services - Zuliarni, Sri; Maharani, Maharani (PT Aksara Indo Rajawali, 2025)
CEISA can facilitate services and supervision by Customs officers in terms of customs and excise. However, there are still DGCE offices that develop applications independently, which means they are not integrated with CEISA. This study aims to apply the EUCS technique at one of the Type A Customs and Excise Supervision and Service Offices in Indonesia to analyse the degree of user trust in the CEISA system. This study employs a quantitative design and utilizes the End-User Satisfaction (EUS) technique to assess user trust in the CEISA system. By distributing surveys, this research employs quantitative approaches to gather data from 100 respondents, namely employees of the Type A Customs and Excise Supervision and Service Office in Indonesia, who are end-users of the CEISA system. The SPSS software was used to analyse the data using multiple linear regression. The findings demonstrated that Content, Format, Ease of use, and Timeliness in the CEISA system have a significant influence on user trust. In contrast, Accuracy in the CEISA system does not have a significant influence on user trust.